2015
DOI: 10.1242/bio.014084
|View full text |Cite
|
Sign up to set email alerts
|

The nature of alarm communication in Constrictotermes cyphergaster (Blattodea: Termitoidea: Termitidae): the integration of chemical and vibroacoustic signals

Abstract: Alarm signalling is of paramount importance to communication in all social insects. In termites, vibroacoustic and chemical alarm signalling are bound to operate synergistically but have never been studied simultaneously in a single species. Here, we inspected the functional significance of both communication channels in Constrictotermes cyphergaster (Termitidae: Nasutitermitinae), confirming the hypothesis that these are not exclusive, but rather complementary processes. In natural situations, the alarm predo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 60 publications
2
52
0
Order By: Relevance
“…In line with this idea, while N. corniger occurrence (reported as Nasutitermes costalis ) on trees was found to be negatively affected even by generalist ants (Jutsum, Cherret, & Fisher, ), the termite's nest density and size distribution were unresponsive to changes in anteater density, suggesting that N. corniger is well adapted to neutralize anteater attacks (Hirsch, Martinez, Kurten, Brown, & Carson, ). While the mechanism behind the latter is not entirely clear, the current findings suggest that colonies exposed to such predators could develop an ever stronger patrolling response as they experience successive structural injuries throughout their ontogeny, mediated by the accumulation of alarm pheromones (Cristaldo et al., ). Thus, colonies that successfully survive several attacks could become effectively “immune.” This could be tested by determining (i) whether patrolling intensity is an increasing function of breaching frequency, and (ii) whether colonies that co‐occur with anteaters (e.g., pristine forest) respond more strongly to breaching than colonies from habitats where such predators no longer exist (e.g., urban forest fragment).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In line with this idea, while N. corniger occurrence (reported as Nasutitermes costalis ) on trees was found to be negatively affected even by generalist ants (Jutsum, Cherret, & Fisher, ), the termite's nest density and size distribution were unresponsive to changes in anteater density, suggesting that N. corniger is well adapted to neutralize anteater attacks (Hirsch, Martinez, Kurten, Brown, & Carson, ). While the mechanism behind the latter is not entirely clear, the current findings suggest that colonies exposed to such predators could develop an ever stronger patrolling response as they experience successive structural injuries throughout their ontogeny, mediated by the accumulation of alarm pheromones (Cristaldo et al., ). Thus, colonies that successfully survive several attacks could become effectively “immune.” This could be tested by determining (i) whether patrolling intensity is an increasing function of breaching frequency, and (ii) whether colonies that co‐occur with anteaters (e.g., pristine forest) respond more strongly to breaching than colonies from habitats where such predators no longer exist (e.g., urban forest fragment).…”
Section: Discussionmentioning
confidence: 78%
“…Upon breaching, soldiers quickly go out and move around for some time, while workers stop foraging and start sealing the breach (Lubin & Montgomery, ; Fontes, ; P. A. C. L. Pequeno, personal observation, September 21, 2015). Such behaviours are coordinated by a combination of chemical and vibroacoustic signals (Cristaldo et al., ). Termites may minimize the risk of colony damage and mortality by anticipating potential predators, similar to vertebrates when engaging in vigilance behaviour.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But while alarm signals in termites are known to be mediated by two different sensorial channels (vibroacoustic and olfactory, see Connétable et al 1999;Röhrig, et al 1999;Reinhard and Clément 2002;Hager and Kirchner 2013), they have never been investigated together in any termite species until recently (Cristaldo et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In termites, all known termite alarm pheromones are used for defensive purpose only and are produced by the frontal gland (Pasteels and Bordereau 1998;Šobotník et al 2010a), an organ unique to Neoisoptera, a group comprising Serritermitidae, Rhinotermitidae and Termitidae (Noirot 1969;Quennedey 1984;Šobotník et al 2010a). Although the chemical alarm communication occurs in many species (CostaLeonardo et al 2009;Šobotník et al 2010a), the alarm pheromones have only been identified in few species, namely in Prorhinotermes canalifrons (Rhinotermitidae), Velocitermes velox, Nasutitermes rippertii, N. corniger, N. princeps and Constricto te rmes cyp hergaste r (all Te rmitidae: Nasutitermitinae) (see Šobotník et al 2010a for a review, Cristaldo et al 2015).…”
Section: Introductionmentioning
confidence: 99%